Investigation of the effectiveness of different roof retrofits for existing one-storey, three-classroom school buildings against severe wind loads using vulnerability curves - Zafra, Ariel Vince C.
Directly facing the Pacific Ocean along the typhoon belt, the Philippines has been frequented by typhoons that variably cause substantial damages and losses to lives, property, agriculture, and infrastructures. With these recurring hazards, school buildings, apart from serving as educational facilities, also serve as evacuation centers for those affected by these calamities. Therefore, it is important for these structures to withstand hazards, or in this case, severe wind events that are expected to happen within its lifetime. However, a trend of increasing wind intensities poses danger to the integrity of the structure and redesign is something deemed impractical and uneconomical especially on already existing structures. Therefore, this study aims to investigate different roof retrofitting schemes that aim to strengthen the resistance of these structures to winds. Retrofitting, as defined in this study, is the addition of components on the structural system to strengthen the structure's resistance against wind loads. In this study, the configurations and vulnerable components of a typical school building were known. Three retrofitting schemes were applied on the base design, considering its feasibility and costs of implementation. The first retrofit method was the addition of roof fasteners to condense the spacing of fasteners along the roof cover. The second retrofit scheme considers the indirect strengthening of the truss supports by adding anchorage reinforcement bars connected to a beam attached to the top chord of the truss. The third retrofit scheme was the direct strengthening of the roof-to-column connections by adding grouted anchor bolts. The performance of the retrofitted designs, along with the base design, against wind loads were assessed by comparing their damage ratios, which were obtained from the damage probabilities, estimated from failure simulation at the onset which used probabilistic resistance capacities on the roof components and deterministic wind speeds from past numerical simulations, and cost factors. Wind vulnerability curves were generated for each wind approach angle in terms of the damage ratio and sustained wind speeds (m/s). Superimposing the vulnerability curves of the base and retrofitted designs reaffirms the conclusion that strengthening the truss supports significantly reduces the damage ratios. Furthermore, a cost-benefit analysis of the retrofit designs against the base design shows that the direct retrofit on the roof-to-column connections by the installation of grouted anchor bolts to the already existing truss supports has been the most efficient of the retrofit methods assessed in this study.